1999
DOI: 10.1385/abab:79:1-3:649
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Saccharification and Cofermentation of Dilute-Acid Pretreated Yellow Poplar Hardwood to Ethanol Using Xylose-Fermenting Zymomonas mobilis

Abstract: Simultaneous saccharification and cofermentation (SSCF) was carried out at approximately 15% total solids using conditioned dilute-acid pretreated yellow poplar feedstock, an adapted variant of National Renewable Energy Laboratory (NREL) xylose-fermenting Zymomonas mobilis and either commercial or NREL-produced cellulase enzyme preparations. In 7 d, at a cellulase loading of 12 filter paper units per gram cellulose (FPU/g), the integrated system produced more than 3% w/v ethanol and achieved 54% conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…Given the proven adeptness of Z. mobilis in industrial-scale fermentation, the ability to express high levels of active cellulases shown in this study and the capacity to secrete these enzymes, the foundation has been laid for further investigations in the establishment of Z. mobilis as a CBP organism. While CBP might be considered the ultimate goal, any significant production of cellulolytic enzymes by Z. mobilis could be considered a success, as this would reduce the required loading levels of exogenously produced cellulases during simultaneous saccharification and fermentation or cofermentation, processes in which Z. mobilis has already been tried and tested (14,24,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the proven adeptness of Z. mobilis in industrial-scale fermentation, the ability to express high levels of active cellulases shown in this study and the capacity to secrete these enzymes, the foundation has been laid for further investigations in the establishment of Z. mobilis as a CBP organism. While CBP might be considered the ultimate goal, any significant production of cellulolytic enzymes by Z. mobilis could be considered a success, as this would reduce the required loading levels of exogenously produced cellulases during simultaneous saccharification and fermentation or cofermentation, processes in which Z. mobilis has already been tried and tested (14,24,36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Z. mobilis has the ability to ferment sugars at low pH and has a naturally high tolerance to many of the inhibitory compounds found in hydrolysates derived from lignocellulosic biomass (45, 46) Furthermore, the use of the Entner-Doudoroff pathway (37) allows Z. mobilis to achieve the near-theoretical maximum ethanol yields during fermentation while achieving relatively low biomass formation. Accordingly, Z. mobilis has been used successfully in SSF and SSCF processes (14,24,36). Additionally, Z. mobilis has been successfully engineered to ferment the pentose (C 5 ) sugars, xylose (45) and arabinose (10).…”
mentioning
confidence: 99%
“…The carbohydrate content of SSO was determined via quantitative saccharification (QS) method based on 2 hours incubation in 72wt% H 2 SO 4 at 30 o C (Ruiz and Ehrman, 1996;McMillan et al, 1999;Moxley and Zhang, 2007). The cell mass was determined by counting colony forming units on agar plates as described in (Zhang et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…This model accounts for cellulose and hemicellulose enzymatic hydrolysis and competitive uptake of glucose and xylose. There are only a few published studies on the conversion of cellulose and hemicellulose via SSCF (McMillan et al, 1999;Teixeira et al, 2000;Kim and Lee, 2005) and only few kinetic models have been proposed in the literature (Shao, 2007, Zhang, 2008. A kinetic model development used in this work was based on a semi-mechanic rate equation for cellulose hydrolysis as initially proposed by (South et al, 1995) and further modified by (Shao, 2007) and (Zhang, 2008) to accommodate cellulose and hemicellulose hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…A process based on the use of Zymomonas mobilis using lignocellulose obtained from hard woods (McMillan et al, 1999) consists of in situ cellulase production to enable simultaneous sacarifi cation and fermentation. The cost estimated for ethanol obtained by this process is 0.36 USD per liter.…”
Section: Some Commercial Processes For Ethanol Production From Lignocmentioning
confidence: 99%